Assessing the influence of isotopic composition of water on that of clay minerals during chemical treatments. - Campaña, Isidoro; Wynn, J.G.; Iglesias-Cibanal, Javier; Benito-Calvo, Alfonso; Álvaro-Gallo, Ana; Bermejo, I; Pérez-González, Alfredo; Bermúdez de Castro, José María (Elsevier, 2022)
The isotopic composition of hydrogen in authigenic minerals is a useful tool to reconstruct past paleo-environments. Clay minerals are an important component of authigenic minerals in soils and sediments but they usually occur with other compounds that must be eliminated before the analysis, such as organic matter and carbonates. Thus, various “pre-treatments” are used, generally involving dilute HCl and H2O2 solutions in water. In this work, the influence of the isotopic composition of the water used in these pre-treatment solutions is assessed, using ten different samples of clay minerals. The isotopic composition of hydrogen was measured in each sample after HCl pre-treatment alone, H2O2 pre-treatment alone and both HCl and H2O2 pre-treatments in sequence, using two types of water in the pre-treatment solutions: one 2H-enriched and one 2H-depleted. The results indicate some influence of the isotopic composition of the water on the clay minerals after pre-treatment. In general, the samples showed significant alteration by HCl pre-treatment and negligible alteration by H2O2 pre-treatment. A pure kaolinite reference material did not show any change by chemical pre-treatment while a smectite reference material did show significant effects. Other samples (Ethiopian lacustrine sediment samples and Spanish cave sediments) showed important differences, which also depend on clay mineralogy. Thus, mineralogy seems to be the main cause of the variability in the alteration, especially the quantity of smectite. In addition, this result challenges the utility of clay minerals for isotope studies in acid conditions, such as in acidic soils, to reconstruct past environments and, therefore, climate changes.
Keywords: Hidrógeno -- Isótopos; Minerales de arcilla; Isótopos estables; Esmectita; Clay minerals; Stable isotopes; Hydrogen; Chemical treatments; Smectite